Analisis Political Will Walikota Banda Aceh dalam Permasalahan Penertiban Pedagang Liar Gampong Rukoh Kecamatan Syiah Kuala - Intan Mardiana; Fadhil Fadhil (CV. Rumoh Aceh Publishing, 2026)
This study aims to analyze the political will of the Mayor of Banda Aceh in the policy of controlling street vendors in Gampong Rukoh, Syiah Kuala District, and to examine the social impacts arising from the policy. The issue of street vendors in this area has become a government concern because it is considered to disrupt public order, the function of public spaces, and environmental comfort in the educational area. This study employs a qualitative method with data collection techniques through interviews and documentation. The informants consisted of officials from the Banda Aceh Mayor's office, Satpol PP officers, gampong officials, academics, community members, and vendors operating in the area. The results indicate that the political will of the Banda Aceh city government in controlling street vendors in Gampong Rukoh has been demonstrated through government responses to public reports, inter-agency coordination, and the issuance of administrative warnings. However, this political will remains responsive and has not been fully supported by technical planning, resource allocation, and consistent sanctions enforcement. In terms of social impact, the street vendor control policy has generated several consequences within the community, including temporary changes in vendor behavior, differing community attitudes between groups that support and oppose the presence of vendors, and an imbalance in the distribution of benefits and social burdens. Additionally, unintended consequences have emerged, such as relocation uncertainty and the persistence of vendors in the original location. Thus, the street vendor control policy in Gampong Rukoh shows that the government's political will exists but is not yet fully robust and still requires more comprehensive policy planning to ensure effective and sustainable implementation.